Stink and the hairy scary spider - McDonald, Megan; Reynolds, Peter H. (Somerville, Massachusetts : Candlewick Press, 2020)
"Stink's spider phobia spurs his sister, Judy, and friend Webster to try some desensitization techniques--until a real-life encounter takes them by surprise--in a hilarious episode offering a bonus origami activity"--Publisher.
Keywords: Spiders -- Juvenile fiction; Brothers and sisters -- Juvenile fiction